PERLINDUNGAN HUKUM BAGI DOKTER PADA PELAYANAN KEGAWATDARURATAN DI RUMAH SAKIT UMUM DAERAH ABDUL WAHAB SJAHRANIE SAMARINDA - Anton Christian Ompu Sunggu (MIH Unsoed, 2016)
The Research purpose to analyze the implementation of law protection for doctors in the emergency service unit at the Abdul Wahab Sjahranie Samarinda and to analyze the solutions applied by the emergency unit to resolve the issues regarding to the law protection. Research methodology uses the ‘yuridis normatif’ approach where the research type to find law ‘in concreto’. The research is conducted at the Abdul Wahab Sjahranie Hospital in Samarinda. Based on the research results, the implementation of law protection for doctros in the emergency unit at the Abdul Wahab Sjahranie Samarinda has been applied according to the Law and Regulation in Indonesia therefore the doctors have practiced the medical actions following the standard operational procedures (SOP). In this case, they are not able to be prosecuted in the event of mistreatment and to resolve the medical dispute, the hospital employs the mediation process called Alternative Dispute Resolution (ADR) according to Articles No. 36 Year 2009 about health chapter 29 that states in the event of negligence by doctors in conducting medical actions, is able to be settled by mediation.Key words : Alternative Dispute Resolution, emergency.